2021
DOI: 10.3390/robotics10020061
|View full text |Cite
|
Sign up to set email alerts
|

FES Cycling and Closed-Loop Feedback Control for Rehabilitative Human–Robot Interaction

Abstract: For individuals with movement impairments due to neurological injuries, rehabilitative therapies such as functional electrical stimulation (FES) and rehabilitation robots hold vast potential to improve their mobility and activities of daily living. Combining FES with rehabilitation robots results in intimately coordinated human–robot interaction. An example of such interaction is FES cycling, where motorized assistance can provide high-intensity and repetitive practice of coordinated limb motion, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…A fundamental research question for the development of hybrid exoskeletons is how to allocate or segregate the control design for the powered actuators and muscles ( Alibeji et al, 2018a ; Alibeji et al, 2018b ; Ha et al, 2016 ). Kinematic tracking has been the primary control objective for rehabilitation devices and machines that combine FES and powered actuation, where the desired trajectories can be tracked by muscles, electric motors (i.e., the machine or robot) or both during walking and cycling ( Alibeji et al, 2018b ; Duenas et al, 2019 ; Cousin et al, 2021 ). Recently, torque tracking objectives have been developed for motorized FES-cycling using admittance-based or impedance-based strategies with a Lyapunov-based analysis ( Chang and Duenas, 2019 ; Duenas et al, 2020 ; Cousin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental research question for the development of hybrid exoskeletons is how to allocate or segregate the control design for the powered actuators and muscles ( Alibeji et al, 2018a ; Alibeji et al, 2018b ; Ha et al, 2016 ). Kinematic tracking has been the primary control objective for rehabilitation devices and machines that combine FES and powered actuation, where the desired trajectories can be tracked by muscles, electric motors (i.e., the machine or robot) or both during walking and cycling ( Alibeji et al, 2018b ; Duenas et al, 2019 ; Cousin et al, 2021 ). Recently, torque tracking objectives have been developed for motorized FES-cycling using admittance-based or impedance-based strategies with a Lyapunov-based analysis ( Chang and Duenas, 2019 ; Duenas et al, 2020 ; Cousin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have addressed closed-loop control strategies to track cadence, torque and power [ 7 , 8 , 9 ]. Besides the performance of the controller and cycling outcomes, the results obtained from investigations indicated that the choice of the strategy to be developed reflects a trade-off between what is expected from the rehabilitation goals and the level of complexity from a technological point of view.…”
Section: Introductionmentioning
confidence: 99%